Human health risk due to trace element contamination in groundwater from the anjani and jhiri river catchment area in northern maharashtra, india (2013)
Abstract: Present study was carried out the assessment of ground water chemistry with reference to drinking purpose. We have selected the area of Anjani and Jhiri river catchment of Jalgaon district, northern Maharashtra, India. We have 10 Ground water samples were collected from different location of two urban areas (Daharangaon and Erandol) and some samples from rural water supply wells during the pre monsoon 2011 and post monsoon 2011. From collected groundwater samples analyzed trace elements by using standard techniques. The ground water pollution which is observed some sites of the study area is mainly due waste disposal and agricultural activities and fossil fuel burning by vehicles. The present investigation based on occurrence of trace elements like Fe, Zn, Cu, Ni, Mn, Pb and Cd in the groundwater samples with concentration range varies from 0 to 0.096 ppm , 0.066 to 0.427 ppm , 0 to 0.012 , 0.026 to 0.361 ppm , 0 to 0.160 ppm, 0.968 to 1.516 ppm and 0 to 1.064 ppm respectively. The analysis of ground water chemistry and obtained results compared with BIS drinking water standards. The concentration of lead, cadmium and Nickel exceeds than the maximum permissible limit as per BIS drinking water standards.